Aplikasi Sensor Cahaya (BH1750) pada Tanaman Anggrek menggunakan ESP 32 Berbasis IoT - rahma, diana mauli (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2025)
Sunlight plays an important role in the photosynthesis process of orchid plants for optimal growth. Cymbidium orchid plants, for example, require a range of sunlight intensity between 3500 lux to 4000 lux (B.V., 2023). When sunlight intensity is low, the photosynthesis process will inhibit orchid plant growth and flower formation (Sudarso et al., 2020). Therefore, it is important to ensure proper light intensity so that orchid plants can grow well. Based on these problems, researchers created a monitoring system and light intensity control system in the smart garden for orchid plants. The device used is an IoT-based ESP32 microcontroller, allowing users to monitor conditions anytime and anywhere via an internet connection. The light sensor used is BH1750 to monitor the intensity of sunlight in the orchid plant area. Blynk is used as an interface to connect the smartphone and the installed hardware. Through Blynk, IoT system developer can control ESP32 in real-time through internet connection. This automation system will work automatically to control the roof and lights based on the input parameters. This research successfully developed the BH1750 sensor application to automate light intensity on orchid plants using ESP32, with monitoring through the Blynk application. Based on the test results, the average accuracy is 99.11%, the average precision is 99.26%, and the average error is 0.15%. Keywords : Blynk, Sunlight, ESP32, IoT, BH1750 Sensor